Optimized nucleus isolation protocol from frozen mouse tissues for single nucleus RNA sequencing application - Minati, Marie-Albane; Fages, Angeline; Dauguet, Nicolas; Zhu, Jingjing; Jacquemin, Patrick (Frontiers in Cell and Developmental Biology, 2023)
The single cell RNA sequencing technique has been particularly used during the last years, allowing major discoveries. However, the widespread application of this analysis has showed limitations. Indeed, the direct study of fresh tissues is not always feasible, notably in the case of genetically engineered mouse embryo or sensitive tissues whose integrity is affected by classical digestion methods. To overcome these limitations, single nucleus RNA sequencing offers the possibility to work with frozen samples. Thus, single nucleus RNA sequencing can be performed after genotyping-based selection on samples stocked in tissue bank and is applicable to retrospective studies. Therefore, this technique opens the field to a wide range of applications requiring adapted protocols for nucleus isolation according to the tissue considered. Here we developed a protocol of nucleus isolation from frozen murine placenta and pancreas. These two complex tissues were submitted to a combination of enzymatic and manual dissociation before undergoing different steps of washing and centrifugation. The entire protocol was performed with products usually present in a research lab. Before starting the sequencing process, nuclei were sorted by flow cytometry. The results obtained validate the efficiency of this protocol which is easy to set up and does not require the use of commercial kits. This specificity makes it adaptable to different organs and species. The association of this protocol with single nucleus RNA sequencing allows the study of complex samples that resist classical lysis methods due to the presence of fibrotic or fatty tissue, such as fibrotic kidney, tumors, embryonic tissues or fatty pancreas.